Pemanfaatan TCS2300 Dalam Media Pembelajaran Balita Pengenalan Warna Berbasis Arduino - Ikhsan Ikhsan; Ratna Mulyana (Jurnal PROCESSOR, 2017)
The writer research the color identification tool with voice output that aims to facilitate children under five to recognize and memorize the colors that are around him and this tool can detect more color than the base color. In this research the writer uses the method of Laboratory Research and Library Research, is to perform direct testing of the equipment to be tested using Arduino Nano and TCS2300 color sensor. From design tool that has been done, then the writer tested the tool by using the Research Laboratory using the programming language. From the results of this test, the color identification tool uses a color sensor with voice output as learning media for children under five year can work as expected. This tool can facilitate children under five to recognize colors, and utilization TCS2300 color sensor is able to detect and distinguish the color of the object by reading the value of the intensity of the color of the object, in this case the object is detected in the form of colored toys.